Racionais MC’s, Marighella, and the Whitening of Brazil - Dutra, Paulo (2020)
In this paper I examine aspects that surround the context of the artistic and intellectual production of representatives of the African diaspora in Brazil. My goal is to highlight how such a production and its reception go through a systematic process of distortion that leads to approaches, analyzes, and conclusions that are based on a process of whitening.